26.032000

How do you find g(x - 3) if g(x)=x² + 2 ?

mrsdarcy1981 Mathematics 2 2

How do you find g(x - 3) if g(x)=x² + 2 ?

Posted by mrsdarcy1981 | Posted at Mar 26, 2000 | Categories: Mathematics

Answers

yassautumn
yassautumn

[latex]g(x-3)=(x-3)^2+2=x^2-6x+9+2=x^2-6x+11[/latex]

Mar 26, 2000 01:20
TamaraTewksbury170
TamaraTewksbury170

To resolve the matter of changing x into (x - 3) ​​in equation : [latex]g(x) = x^{2} + 2[/latex] [latex]g(x-3) = (x-3)^{2} + 2[/latex] [latex]g(x-3) = x^{2}-6x +9 + 2[/latex] [latex]oxed{g(x-3) = x^{2}-6x +11}[/latex]

Mar 26, 2000 01:24

Leave a answer